131k views
1 vote
Please help me with this problem!!! I have been trying to figure it out for the past hour and I still can’t figure it out. Thanks for your help and have a nice day!!!

Please help me with this problem!!! I have been trying to figure it out for the past-example-1
User Neok
by
4.6k points

2 Answers

1 vote

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️


\frac{ {6}^(8) * {6}^(3) }{ {6}^(5) } = \\


\frac{ {6}^(8 + 3) }{ {6}^(5) } = \\


\frac{ {6}^(11) }{ {6}^(5) } = \\


{6}^(11) * {6}^( - 5) =


{6}^(11 - 5) =


{6}^(6)

Thus ;


{6}^([6]) \\

♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️♥️

User Jacek Francuz
by
5.2k points
3 votes
?=6
It says my answer needs to have more characters, so I’m just adding this
User Diti
by
4.4k points